PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRT) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SD NEGERI 003 PAGARAN TAPAH DARUSSALAM ROKAN HULU - Harianja, Tiorunggu (EDUTECH CONSULTANT, 2017)
This research was motivated by the low low reading comprehension class V SD Negeri 003 Pagaran Tapah Darussalam Rokan Hulu. This study aims to improve students' reading comprehension class V SD Negeri 003 Pagaran Tapah Darussalam Rokan Hulu with the implementation of cooperative learning model of integrated reading and composition. The research subjects were 34 students in the academic year 2015-2016. Form of research is classroom action research. Data collection techniques used were observation techniques using observation sheet activities of teachers and students, engineering test reading comprehension. Based on the results, it can be concluded that the application of cooperative learning model of integrated reading and composition can improve students' reading comprehension on the subjects Indonesian Elementary School fifth grade students 003 Pagaran Tapah Darussalam Rokan Hulu. This is evidenced by an increase in average reading comprehension scores of students from primary to the first cycle of a score of 5.56 points and basic to the second cycle of 23.95 points.